RANCANG BANGUN SISTEM INFORMASI PENDAFTARAN ARTIS BERBASIS WEB MENGGUNAKAN MODEL WATERFALL (STUDI KASUS : TEAM MANAGEMENT AGENSI) - Ade Suryanto (Jurnal Khatulistiwa Informatika, 2016)
The rapid development of information technology today is making changes to all aspects of life. Every second of it always us to see and feel its development, especially software that became the main focus. It also followed the development of hardware that is always also a supporting factor. Development of Internet technology that is faster and more users now become a leading-edge technology to deliver things, like send and retrieve media files or documents such as text, video, images, etc. The Internet is also used to convey information, exchange data, media communication between users worldwide. In this paper, the authors use the waterfall model to resolve the existing problems in the agency management team in terms of registration of new artists by applying several stages and procedures. Waterfall method has several steps to resolve the problem include the planning, analysis, design, implementation or application, testing and maintenance is expected to resolve the existing problems in the artist agency Management Team. The results of this study may be the best solution for this agency.Keyword: Artist Agency System Information, Agency